Effects of creatine supplementation on body composition, strength, and sprint performance - Kreider, R. B.; Ferreira, M.; Wilson, M.; Grindstaff, P.; Plisk, S.; Reinhardy, J.; Cantler, E.; Almada, A. L. (Medicine & Science in Sports & Exercise, 1998)
The addition of creatine to the glucose/taurine/electrolyte supplement promoted greater gains in fat/bone-free mass, isotonic lifting volume, and sprint performance during intense resistance/agility training.